2016
DOI: 10.18632/oncotarget.12806
|View full text |Cite
|
Sign up to set email alerts
|

KRAS-mutation status dependent effect of zoledronic acid in human non-small cell cancer preclinical models

Abstract: BackgroundIn non-small cell lung cancer (NSCLC) KRAS-mutant status is a negative prognostic and predictive factor. Nitrogen-containing bisphosphonates inhibit prenylation of small G-proteins (e.g. Ras, Rac, Rho) and thus may affect proliferation and migration. In our preclinical work, we investigated the effect of an aminobisphosphonate compound (zoledronic acid) on mutant and wild type KRAS-expressing human NSCLC cell lines.ResultsWe confirmed that zoledronic acid was unable to inhibit the prenylation of muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Although the incidence of SREs was not decreased by OIs in the present SCLC patients with BM, likely reflecting retrospective treatments, new incidences of SREs were observed in 10 of the 23 OIs treated patients, suggesting that OIs prolong survival via a mechanism that is independent of the suppression of SREs. In agreement, Zol reportedly suppressed the proliferation of SCLC cell lines in vitro and in vivo (17,18), and these antitumor effects of Zol were associated with inhibition of farnesylation and geranylgeranylation of RAS related proteins, and the induction of apoptosis (17). Zol also showed synergistic effects with other anti-cancer agents, such as cisplatin, etoposide and irinotecan in vitro (19)(20)(21), and a recent preclinical study showed that Zol promotes the maturation of γδ T cells and contributes to antitumor immune responses (22).…”
Section: Prior To Psm (N) Following Psm (N) -------------------------supporting
confidence: 63%
“…Although the incidence of SREs was not decreased by OIs in the present SCLC patients with BM, likely reflecting retrospective treatments, new incidences of SREs were observed in 10 of the 23 OIs treated patients, suggesting that OIs prolong survival via a mechanism that is independent of the suppression of SREs. In agreement, Zol reportedly suppressed the proliferation of SCLC cell lines in vitro and in vivo (17,18), and these antitumor effects of Zol were associated with inhibition of farnesylation and geranylgeranylation of RAS related proteins, and the induction of apoptosis (17). Zol also showed synergistic effects with other anti-cancer agents, such as cisplatin, etoposide and irinotecan in vitro (19)(20)(21), and a recent preclinical study showed that Zol promotes the maturation of γδ T cells and contributes to antitumor immune responses (22).…”
Section: Prior To Psm (N) Following Psm (N) -------------------------supporting
confidence: 63%
“…Notably, however, a recent preclinical study demonstrated that the aminobisphosphonate compound zoledronic acid was ineffective in NSCLC cells harboring exon 2 codon 12 KRAS mutation, since this mutational subtype leads to prenylation-independent activation of KRAS. [80]. Nevertheless, the impact of the bisphosphonate treatment in KRAS-mutant LADC patients remains to be fully explored.…”
Section: Targeting Kras Membrane Anchoragementioning
confidence: 99%
“…Under these conditions, 1, 3 and 10 µM Zol significantly slows down the proliferation at a range of 20 to 80% for all cell types with BML4 having the highest sensitivity. These Zol doses were up to 100 times less than the concentrations previously used to decrease proliferation of human NSCLC including HCC827 and SCLC cell lines (in vitro for less than 5 days) [35,36,37,45]. In all these studies, the impaired proliferation was attributed either to an increase in cell apoptosis or to a disruption of cell cycle [35,36,37,45].…”
Section: Discussionmentioning
confidence: 99%
“…These Zol doses were up to 100 times less than the concentrations previously used to decrease proliferation of human NSCLC including HCC827 and SCLC cell lines (in vitro for less than 5 days) [35,36,37,45]. In all these studies, the impaired proliferation was attributed either to an increase in cell apoptosis or to a disruption of cell cycle [35,36,37,45]. Moreover, it was suggested that bisphosphonates promote apoptosis in the bone-colonizing cancer cells as a result of restricting the supply of bone-stored growth factors that are crucial for the proliferation and survival of cancer cells following the inhibition of osteoclastic bone resorption [46,47,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%